2022
DOI: 10.1186/s40824-022-00313-2
|View full text |Cite
|
Sign up to set email alerts
|

Recent biomedical advancements in graphene oxide- and reduced graphene oxide-based nanocomposite nanocarriers

Abstract: Recently, nanocarriers, including micelles, polymers, carbon-based materials, liposomes, and other substances, have been developed for efficient delivery of drugs, nucleotides, and biomolecules. This review focuses on graphene oxide (GO) and reduced graphene oxide (rGO) as active components in nanocarriers, because their chemical structures and easy functionalization can be valuable assets for in vitro and in vivo delivery. Herein, we describe the preparation, structure, and functionalization of GO and rGO. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 209 publications
0
29
0
Order By: Relevance
“…36,52,53 A detailed discussion on the synthesis and structural models of GO is beyond the scope of this manuscript and can be found elsewhere. 31,32 Inspired by studies reporting ODs in CNTs, Rourke et al 25 performed a similar base-washing in GO dispersions and found that ODs were present. They also found that ODs accounted for ca.…”
Section: Go Production and The Emergence Of Odsmentioning
confidence: 99%
See 2 more Smart Citations
“…36,52,53 A detailed discussion on the synthesis and structural models of GO is beyond the scope of this manuscript and can be found elsewhere. 31,32 Inspired by studies reporting ODs in CNTs, Rourke et al 25 performed a similar base-washing in GO dispersions and found that ODs were present. They also found that ODs accounted for ca.…”
Section: Go Production and The Emergence Of Odsmentioning
confidence: 99%
“…36,52,53 A detailed discussion on the synthesis and structural models of GO is beyond the scope of this manuscript and can be found elsewhere. 31,32…”
Section: Go Production and The Emergence Of Odsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggested that Rp@Al exhibited a potent anti-biofilm efficiency against MRSA through its photothermal effect. Local hyperthermia may destroy bacterial structures by producing ROS or denaturing protein structure, ultimately resulting in bacterial death [57]. Hence, DCFH-DA staining was performed to reveal the ROS levels in the MRSA after the various treatments (Fig.…”
Section: Photothermal Antibacterial Activity Of Rp@al In Vitromentioning
confidence: 99%
“…Novel uorogenic probes have been actively studied to achieve enhanced uorescence microscopy [18][19][20][21]. In particular, carbon nanoparticles (CNPs) have been investigated as cell imaging probes because of their superior biological and physicochemical properties when compared with those of conventional dyes [22][23][24][25]. Furthermore, CNPs have exceptional biological prospects in controlling cellular behaviors, including adhesion, migration, proliferation, differentiation of cells into speci c lineages, and maturation of progenitor cells [26][27][28][29][30].…”
mentioning
confidence: 99%